Evaluation of Gestational Diabetes Mellitus Risk in South Indian Women Based on MTHFR (C677T) and FVL (G1691A) Mutations - Khan, Imran Ali; Shaik, Noor Ahmad; Kamineni, Vasundhara; Jahan, Parveen; Hasan, Qurratulain; Rao, Pragna (Frontiers in Pediatrics, 2015)
We aimed to scrutinize the extent to which single amino acid substitutions in the MTHFR and FVL genes affect the risk of GDM in pregnant women of South Indian descendant. This case-control study was implemented once the ethical approval has been obtained. Overall 237 women were recruited in this study: 137 had been diagnosed with GDM and the remaining 100 women were used as normal controls or non-GDM. The diagnosis of GDM was confirmed with biochemical analysis i.e., GCT and OGTT tests. Five milliliters of peripheral blood was collected and used for biochemical and molecular analyses. DNA was isolated and genotyping for MTHFR (C677T) and FVL (G1691A) mutations was performed using PCR-RFLP. FVL (G1691A) locus was not polymorphic in the investigated sample. There was no significant difference in the allele and genotype frequencies of C677T polymorphism between GDM and non-GDM women (p=0.8892)